Analisis Keadilan Restoratif (Restorative Justice) dalam Konteks Ultimum Remedium sebagai Penyelesaian Permasalahan Tindak Pidana Anak - Bambang Hartono (PRANATA HUKUM, 2015)
In Indonesia ,The meaning of Restorative Justice is a fair thing Completion Operations involving Performers , Victims , their family and other party who related the Crime. The Problems on Research Implementation What is Restorative Justice in the Context of ultimum Remedium As abuse child and what is the detention factor of Restorative Justice Implementation of abuse child. Based on the research is that implementation of Justice in the Context ultimum Remedium as settlement of abuse child is the protection of the children's rights had dealed with law. The detention factor of Restorative Jusice implementation have not legitimation in law and be basedon take decision of investigation process